Violence & Conflict Studies (Analyze the role and motive of Sampang trichotomy of power on attack and expulsion Conflict of Shia followers in Blu’uran and Karanggayam villages) - Abdullah Binzed (IPEM 15 UMY 251, 2015)
*251